Suggested Medical Hydrology Speciality Program - Maraver, Francisco; Álvarez, Antonio; Gómez, Fernando; Romero, Margarita; Meijide, Rosa; Armijo, Francisco (Anales de Hidrología Médica, 2012)
This paper arises from the National Medical Hydrology Committee’s assignment to the authors to design a draft program for the speciality that complies with the order 44/2003 applied to health professions. The text has been completely written by the Professional School of Medical Hydrology of the Complutense University of Madrid during the first quarter of 2009. The educational programs of Labor Medicine and Family and Communitarian Medicine, as well as, the Work program on the Educational Plan for Physical Education and Sports residents have been a reference for this paper. The draft proposes ten main chapters: denomination, historic introduction and context, definition, objectives, teaching methodology, structure and contents, provision, resident responsibility levels, person responsible for the residents’ education and evaluation; and three appendix containing the plan’s structure and contents, the educational chronogram, and the complementary formation as well as a nomenclator